The Nucleocapsid Protein Of Newcastle Disease Virus As A Carrier For The Vp1 Polypeptides Of Enterovirus 71 - Sivasamugham, Lalita Ambigal (2005)
Human enterovirus 71 (EV71) is an important human enterovirus which belongs to the Enterovirus genus of the Picornaviridae family. Large outbreaks of EV71 have been associated with severe central nervous disease (CNS) manifestations including the hand, foot and mouth disease (HFMD). To date, there is no effective antiviral drug available to treat the infections. Therefore, the development of an effective vaccine is considered as one of the best choice to prevent the diseases caused by EV71. The VP1 protein which is the most immunogenic capsid protein of EV71, can be used in the development of subunit EV71 vaccines. The complete VP1 protein of EV71 was truncated into six regions and fused to the full length nucleocapsid protein (NPfl) and truncated NP (NPt; which lacks 20% amino acids from its Cterminal end). Western blot analysis using rabbit anti-VP1 serum showed that the N-terminal region of the VP1 protein contained a major antigenic region. Of all the recombinant NP proteins, the ones carrying truncated VP1 protein, VP11-100 were efficiently expressed in Escherichia coli system. Electron microscopic analysis of the purified NPt-VPl-loo revealed that this protein predominantly selfassembled into intact ring-like structure whereas NPfl-VPl-loo showed disrupted ring-like formations. Rabbits immunized with these purified recombinant proteins exhibited a strong immune response against the complete VP1 protein. The antisera of these recombinant proteins also reacted positively with the authentic EV71 when analyzed by an immuno flourescence assay thus suggesting their potential as subunit vaccine candidates against EV71 infections and also as immunological reagents for the detection of anti-EV71 antibodies in serum samples.